PRIMARY EXAMPLES (Romanian Journal of Analytic Philosophy, 2025)
As characterized here, primary examples are universal judgements which make the connection between theory and natural language, and contribute to the instantiation of a theory or a whole research domain. They are segments of reasoning that are constructed from perceptual states had as part of wide-ranging experiences accessible to those thinkers who encounter primary examples.There are at least three traits that Primary Examples must have in order to be considered as such. Primary examples must be pertinent to a theory, to the point of being fully inserted and implemented in the theory. Primary examples must exhibit generality, where generality is seen as the template for a general dynamic hidden in space-time and revealed by primary examples. Primary examples must be convincing, to the point that by nature of their perceptual states, their reasoning should prove undeniable, as opposed to abstract principles and notions.In order to prove the merit of primary examples, I will refer to the literature on objectivity in science and show how primary examples are employed in scientific experiments.
Keywords: primary examples; ordinary examples; pertinence; generality; convincing character; interdisciplinarity; theory-starting perceptions